Impacts of the Osmolality and the Lumenal Ionic Strength on Osmosensory Transporter ProP in Proteoliposomes - Culham, Doreen E. (American Society for Biochemistry and Molecular Biology, 2012)
H(+) symporter ProP serves as a paradigm for the study of osmosensing. ProP attains the same activity at the same osmolality when the medium outside cells or proteoliposomes is supplemented with diverse, membrane-impermeant solutes. The osmosensory mechanism of ProP has been probed by varying the solvent within membrane vesicles and proteoliposomes. ProP activation was not ion specific, did not require K(+), and could be elicited by large, uncharged solutes polyethylene glycols (PEGS). We hypothesized that ProP is an ionic strength sensor and lumenal macromolecules activate ProP by altering ion activities. The attainable range of lumenal ionic strength was expanded by lowering the phosphate concentration within proteoliposomes. ProP activity at high osmolality, but not the osmolality, yielding half-maximal activity (Π(½)/RT), decreased with the lumenal phosphate concentration. This was attributed to acidification of the proteoliposome lumen due to H(+)-proline symport. The ionic strength yielding half-maximal ProP activity was more anion-dependent than Π(½)/RT for proteoliposomes loaded with citrate, sulfate, phosphate, chloride, or iodide. The anion effects followed the Hofmeister series. Lumenal bovine serum albumin (BSA) lowered the lumenal ionic strength at which ProP became active. Osmolality measurements documented the non-idealities of solutions including potassium phosphate and other solutes. The impacts of PEGS and BSA on ion activities did not account for their impacts on ProP activity. The effects of the tested solutes on ProP appear to be non-coulombic in nature. They may arise from effects of preferential interactions and macromolecular crowding on the membrane or on ProP.